Congenital Myopathy of Neonatal Onset - A Case Report - Fatima Jehangir; Rabia Faisal; Arwa Giani; Zainab Aziz (ziauddin University, 2024)
Congenital myopathies (CMs) are a diverse group of rare inherited muscle disorders characterized by muscle weakness and hypotonia. Very few studies have outlined the cases of CM in Pakistani immigrant families. The following is a case of a premature male neonate who was born with global hypotonia, cryptorchidism and scoliosis. He was vitally stable at birth, but his respiratory function deteriorated over time and was on ventilatory support. Chest X-rays suggested atelectasis while lab findings revealed deranged arterial blood gas (ABG) and abnormal complete blood count (CBC) levels. Creatine kinase levels were normal however; electrocardiogram (ECG) showed atrial defect and right ventricle and pulmonary artery hypertension. Nerve conduction studies (NCS) and electromyography (EMG) results were suggestive of Myopathy. The patient succumbed to respiratory failure 12 days after birth. Due to the low incidence of CMs and their variable presentation, it is easy to misdiagnose and hence, this delays the timely and effective intervention. Keywords: Congenital Myopathy; Arterial Blood Gases; Electromyography; Nerve Conduction Studies.